Design of Routing Home Gateway in Large-Scale Commercial Engineering Deployment of IPv6 - Peiliang Sun; Xiang Zhou; Zhonghua Chen (Dianxin kexue)
By analyzing the technology evolution of IPv6 in the deployment of IPng, indicate the difficulties to CP in large-scale deployment of IPv6 terminals. Combined with HG's key role in IPv6 network construction, the technical principle of HG was analyzed, the technical advantages of routing HG in large-scale deployment of IPv6 terminals were explained, and an implementable scheme was proposed to help CP, and the whole industry, to speed up the scale deployment of IPv6.